A statistical comparison of the optical/UV and X-ray afterglows of gamma-ray bursts using the Swift Ultraviolet Optical and X-ray Telescopes - Oates, S.; Page, M.; Schady, P.; De Pasqualea, M.; Evans, P.; Page, K.; Chester, M.; Curran, Peter; Koch, T.; Kuin, N.; Roming, P.; Siegel, M.; et al. (Oxford University Press, 2011)
We present the systematic analysis of the Ultraviolet/Optical Telescope (UVOT) and X-rayTelescope (XRT) light curves for a sample of 26 Swift gamma-ray bursts (GRBs). By comparingthe optical/UV and X-ray light curves, we found that they are remarkably different during thefirst 500 s after the Burst Alert Telescope trigger, while they become more similar during themiddle phase of the afterglow, i.e. between 2000 and 20 000 s.If we take literally the average properties of the sample, we find that the mean temporalindices observed in the optical/UV and X-rays after 500 s are consistent with a forwardshockscenario, under the assumptions that electrons are in the slow cooling regime, theexternal medium is of constant density and the synchrotron cooling frequency is situatedbetween the optical/UV and X-ray observing bands. While this scenario describes well theaveraged observed properties, some individual GRB afterglows require different or additionalassumptions, such as the presence of late energy injection.We show that a chromatic break (a break in the X-ray light curve that is not seen in theoptical) is present in the afterglows of three GRBs and demonstrate evidence for chromaticbreaks in a further four GRBs. The average properties of these breaks cannot be explained interms of the passage of the synchrotron cooling frequency through the observed bands, nora simple change in the external density. It is difficult to reconcile chromatic breaks in termsof a single component outflow and instead, more complex jet structure or additional emissioncomponents are required.